Rose Flower Petal Showering: Explosion Brings Sorrows at Auspicious Marriage Ceremony - Sudha, R; Babu, V Jayasurya Prasad; Sravan , D (Journal of Indian Academy of Forensic Medicine, 2015)
As a part of custom and tradition, rose flower petals are showered at guests of auspicious ceremony. At one of such ceremony nitrogen gas cylinder (part of equipment used for showering flower petals) exploded; lead to massive explosion injury to the young male operating the compressed gas cylinder of Nitrogen. At about 08:30pm, 30 May 2013, deceased, who was assisting his father in operating above said machine opened the valve accidentally and the compressor filled with Nitrogen gas blasted causing massive disruption of the abdominal area of the deceased who was closer to that machine. His father who was away sustained minor injuries. He died on the spot due to massive blast injury of the abdomen. His spot death made the ceremony tragic to the extent that host changed the venue to continue. As such Nitrogen gas is non inflammable and its non industrial explosions are very far and few of off. Due to rarity of its kind and having potential of being a preventable accident the case is presented in detail.